(untitled) (Research, Society and Development, 2021)
It is necessary to promote the rational use of medications through actions that regulate their prescription, dispensing and consumption. Therefore, the growing use of anxiolytics is worrisome, especially with regard to their irrational use, which can lead to tolerance, chemical dependency and withdrawal syndrome. This research aims to describe the uses of anxiolytic drugs sold in a Family Pharmacy in Southwest Bahia. This is a descriptive and cross-sectional study, using a quantitative approach. The data was collected through a questionnaire answered by the users of these drugs, in August and September 2021. The data analysis was performed using the Statistical Package for the Social Sciences version 22.0, and presented as absolute and relative frequency for the categorical variables, in addition to mean and standard deviation for the continuous variables. As a result, the study was able to identify the profile of the chronic user of benzodiazepines: a person with an average age of 53.87 (± 11.10) years, with a predominance of females (59.34%), with low purchasing power and low education level. The most used drug was Clonazepam and the most indicated pathology, insomnia. It is expected that the data obtained from this research could contribute to implement conducts and measures that promote its rational use and could also assist in the implementation of treatment alternatives aimed at improving the quality of life of these patients, including the adoption of non-pharmacological actions.